Modifiable Risk Factors Including Self-Perceived Stress for Breast Cancer in Hong Kong: A Case-Control Study of 10 757 Subject - Winnie Yeo; Lok-Wa Yuen; Kelvin Kam-Fai Tsoi; Emily Ying-Yang Chan; Carol C Kwok; Inda Soong; Ting-Ying Ng; Joanne Chiu; Miranda Chan; Sharon Wing-Wai Chan; Ting-Ting Wong; Yolanda Ho-Yan Chan; et al. (Clinical Medicine Insights: Oncology)
Background: In Hong Kong, breast cancer is the commonest female cancer. In addition to intrinsic risk factors that cannot be modified, other factors may be potentially modifiable. The objective of this report was to determine modifiable risk factors in association with breast cancer among Chinese women in our locality. Methods: This is a case-control study that enrolled breast cancer patients from the Hong Kong Breast Cancer Registry and healthy matched controls from the local community between 2014 and 2017. Potential risk factors were analyzed using multiple logistic regression. Results: In total, 5186 breast cancer patients and 5571 controls were recruited. Several modifiable risk factors were identified. Self-perceived high stress level (adjusted odd ratios [AOR]= 3.44; 95% confidence intervals [CI] = 3.13-3.78), dairy-rich diet (AOR = 3.33; 95% CI = 2.01-5.52), delayed child-bearing (AOR = 2.23; 95% CI = 1.79-2.79), meat-rich diet (AOR = 1.77; 95% CI = 1.54-2.04), ever use of oral contraceptives (AOR = 1.34; 95% CI = 1.22-1.47), nulliparity (AOR = 1.21; 95% CI = 1.08-1.35), and being overweight/obese (AOR = 1.21; 95% CI = 1.10-1.32) were found to be associated with an increased risk of breast cancer. On the other hand, breastfeeding (AOR = 0.76; 95% CI = 0.69-0.83) and exercise (odds ratio = 0.62; 95% CI = 0.56-0.68) were associated with decreased risk. Conclusions: In our locality, high-stress level, meat- and dairy-rich diet, reproductive history, use of oral contraceptives, and being overweight/obese were identified to be modifiable risk factors for breast cancer. Lifestyle modification may help reduce breast cancer incidence in the coming decades.